SENP1 Aberrance and Its Linkage to Clinical Features, Adjuvant Regimen, and Prognosis in Patients With Surgical Non-small Cell Lung Cancer Receiving Adjuvant Chemotherapy - Yang, Qian; Yang, Mengmeng; Zhang, Jun; Ma, Yuquan (Frontiers in Surgery, 2022)
Background: Small ubiquitin-like modifier-specific protease 1 (SENP1) plays vital roles in cancer progression and chemoresistance, but its prognostic value in non-small cell lung cancer (NSCLC) is vague. This study aimed to explore the correlation of SENP1 with clinical features, adjuvant chemotherapy regimen and prognosis in surgical NSCLC patients receiving adjuvant chemotherapy. Methods: Tumor and adjacent tissues were collected from 157 surgical NSCLC patients receiving adjuvant chemotherapy. Meanwhile, tumor tissue and paired adjacent tissue specimens were obtained to evaluate SENP1 protein expression by immunohistochemistry (IHC) assay; among which 102 pairs were used to detect SENP1 mRNA by reverse transcription quantitative polymerase chain reaction. Results: SENP1 IHC score and SENP1 mRNA expression were increased in tumor tissue than adjacent tissue (both P<0.001). Besides, elevated SENP1 IHC score was correlated with >5cm tumor size (P=0.045), lymph node metastasis occurrence (P=0.003) and advanced TNM stage (P=0.012); meanwhile, increased SENP1 mRNA expression associated with histopathological subtype (P=0.011), lymph node metastasis occurrence (P=0.008) and higher TNM stage (P=0.015). Besides, no correlation was found in SENP1 IHC score (P=0.424) or mRNA expression (P=0.927) with specific adjuvant chemotherapy regimen. Additionally, both SENP1 protein high (P=0.003) and mRNA high (P=0.028) were correlated with poor DFS, while SENP1 protein high was also associated with shorter OS (P=0.029). Furthermore, SENP1 protein (high vs. low) independently associated with unsatisfying DFS (P=0.009, hazard ratio (HR)=1.798) and OS (P=0.049, HR=1.735). Conclusion: SENP1 may serve as a potential biomarker to improve the management of surgical NSCLC patients receiving adjuvant chemotherapy.